Economic analysis of the underground coal gasification (ucg) in Indonesia - Ali Setiawan, Ganjar; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2018)
Abstract. Indonesia has been facing dramatic changes in natural gas industry development, which contributes to economic prosperity and reduces reliance on petroleum fuels. Indonesia's gas markets will continually growth to support economy development. Resources availability and government eagerness to utilise more on natural gas will lead Indonesia to become one of the major gas consumers in the future. This is the potential market for natural gas industry and also an opportunity for natural gas Company to accelerate the company's business growth. This study aims to identify conditions that might occur in the natural gas business industry in Indonesia for the next five years using a scenario planning approach. This is very useful to anticipate possible implications that will arise on the natural gas industry, so that PT. Natural Gas (â€œPNGâ€) can prepare business solutions for conditions that might occur. This scenario planning process started by exploring the natural gas industry condition in Indonesia using the SWOT analysis (Strength, Weakness, Opportunity, and Threat). To be more profound, external environment analysis done by Porter five forces and PESTELÂ  (Politic, Economy, Social, Technology, Environment and Legal) analysis methods, while the internal analysis uses the VRIN (Valuable, Rare, Inimitable, Non substitutable) method. All of these analyses were used to understand how PNG run the businesses, why, where, and when. Based on the results of business analysis and conducting interviews with those who directly involved in the natural gas industry, two key driving forces that greatly affected the natural gas business in Indonesia were found, namely infrastructure and natural gas prices. From here, four scenarios arise about the natural gas industry possible condition in Indonesia. Finally, a strategy recommendation appears that is suitable to be applied for each possible condition. Things that needs to be done is to conduct an external conditions evaluation continuously and identify signals that arise from the external factors and focus on trends that occur compared to signpost in each scenario.Keyword: Scenario planning, business strategy, infrastructure, natural gas price, economic growth.